ANALISIS SEJARAH DAN PERKEMBANGAN TEORI UTILITARIANISME TERHADAP HUKUM INDONESIA - Taufik, Andi Darma; Wahyuni, Fitri; Gunawan, Hendra (Yurisprudentia: Jurnal Hukum Ekonomi, 2024)
There are several schools of legal thought in philosophy, including the Natural Law School, the Positive Law School, the Utilitarian Law School, the Historical School, and others. All schools of law have their own concepts as a basis for making laws. In its actualization, these various legal schools exist in the lives of many people, both the international community and Indonesian society. Utilitarianism places benefit as the goal of law. What is meant by usefulness is happiness. Whether a law is good or not really depends on whether the law makes humanity happy or not. This Utilitarian school was pioneered by Jeremy Bentham (1748 – 1832), a philosopher, jurist economist and legal reformer. Bentham was able to weave the "thread" of the principle of utility into a broad ethical and legal doctrine known as utilitarianism. A law can only be recognized as law if it provides the greatest benefit to the greatest number of people. This principle was put forward by Bentham in his work Introduction to the Principles of Morals and Legislation (1789), which stated that law aims at "the greatest happiness for the greatest number". Lawmakers in drafting laws must involve looking for ways to realize "good". Lawmakers must take into account the fact that the actions they wish to prevent are “bad” or “criminal.”